Organizational Commitment, Teachers' Empowerment, and Transformational Teaching of Public Elementary Schools in Laguna, Philippines - Chayna Glenn R. Blanco; Lerma P. Buenvinida; Consorcia S. Tan; Alberto D. Yazon; Lustina P. Lapie (International Journal of Emerging Issues in Early Childhood Education, 2022)
Teacher commitment is indeed an internal factor that motivates teachers to put more effort and energy into sustaining school involvement and to further improve and enhance their teaching strategies to attain their objectives. Thus, it is important to know the level of commitment, teachers' empowerment, and transformational teaching of teachers during this time of the pandemic. Transformational teaching entails developing dynamic interactions between teachers, students, and a body of shared knowledge. According to this viewpoint, teachers serve as intellectual coaches who construct student teams that work together with their teachers to master bodies of knowledge. These constructivist-based transformational teaching approaches help students develop new knowledge and actions. Teachers that employ constructivist theory as a theoretical framework assist students in becoming active participants in society and the global workplace. The sample of the study consisted of 551 teachers who responded on a representative of public elementary schools in Calamba, Cabuyao, Binan, and Sta. Rosa. Cluster sampling was used to collect the sample, and the city school districts served as the representative of the clusters. Ranking sampling was used to choose the participating schools and the teacher respondents. Each cluster was ranked based on population distribution and gender distribution to maintain an equal proportion of teachers' respondents across all participating schools in the four city school divisions. Teacher respondents were selected randomly to represent the sample of the study. The study mainly focuses on the level of organizational commitment, teachers’ empowerment to the level of transformational teaching. The findings showed that the components of organizational commitment and teachers' empowerment significantly foresee the relationship on transformational teaching of teachers in the four (4) City Schools Division in Laguna. As a result, when teachers demonstrate a high level of organizational commitment and teacher empowerment to the level of transformational teaching, it encourages teachers to stay committed to their field of work and expected to attain their objectives.